2017
DOI: 10.1177/0014402917708216
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum-Based Measurement of Reading Growth: Weekly Versus Intermittent Progress Monitoring

Abstract: We examined the idea that leaner schedules of progress monitoring (PM) can lighten assessment demands without undermining decision-making accuracy. Using curriculum-based measurement of reading, we compared effects on decision accuracy of 5 intermittent PM schedules relative to that of every-week PM. For participating students with high-incidence disabilities—all receiving special education reading instruction ( N = 56)—intermittent schedules of PM performed as well as every-week PM. These findings signal a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(98 citation statements)
references
References 26 publications
4
93
1
Order By: Relevance
“…Whereas less frequent progress monitoring might run the risk of detecting a need for instructional change too late, Jenkins and Terjeson () found that reduced frequency, along with ambitious long‐term goals and use of trend‐based decision rules, actually led to more prompts to modify instruction in reading. Further, Jenkins, Schulze, Marti, and Harbaugh () found no evidence that intermittent progress monitoring schedules (e.g., two or three CBM forms administered on one occasion every two to six weeks) would change decision‐making accuracy compared to weekly CBM administration. However, they cautioned that replication is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas less frequent progress monitoring might run the risk of detecting a need for instructional change too late, Jenkins and Terjeson () found that reduced frequency, along with ambitious long‐term goals and use of trend‐based decision rules, actually led to more prompts to modify instruction in reading. Further, Jenkins, Schulze, Marti, and Harbaugh () found no evidence that intermittent progress monitoring schedules (e.g., two or three CBM forms administered on one occasion every two to six weeks) would change decision‐making accuracy compared to weekly CBM administration. However, they cautioned that replication is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Jenkins and colleagues (2017) hypothesized that intermittent PM schedules could decrease time commitments related to assessment administration and, therefore, enhance the feasibility of using CBM and the DBI process for teachers. Jenkins et al argued that decreasing the time demands related to CBM administration would provide more time for teachers to use the data to inform instruction, particularly for students with inadequate response to intervention.…”
Section: Considering Alternative Pm Schedules: Jenkins Et Al (2017)mentioning
confidence: 99%
“…Jenkins et al (2017) administered three ORF probes each week to 56 students (demographics in Table 1). From the total set of 42 passages administered to each student, Jenkins et al simulated six PM schedules (i.e., one a week, two every 2 weeks, and three every 3, 4, 5, and 6 weeks).…”
Section: Considering Alternative Pm Schedules: Jenkins Et Al (2017)mentioning
confidence: 99%
See 2 more Smart Citations